2018
DOI: 10.21053/ceo.2017.01060
|View full text |Cite
|
Sign up to set email alerts
|

The Allele 2 of the VNTR Polymorphism in the Gene That Encodes a Natural Inhibitor of IL-1β, IL-1RA Is Favorably Associated With Chronic Otitis Media

Abstract: Objectives Chronic otitis media (COM) is followed by irreversible tissue damage and destruction of the middle ear structures, with the possibility of complications under the maintenance of inflammation. Inflammatory mediators such as cytokines play a crucial role in the initial stage of inflammation. The aim of this study was to evaluate the association of the polymorphisms in two innate immunity/inflammation cascade genes from interleukin-1 (IL-1) gene cluster with COM with regard to cholesteatoma.Methods In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…According to some studies the carriers of IL-1RN *2 have higher IL-1RA levels (53,55,56), and consequently the 2 allele effects could down-regulate IL-1 mediated pro-inflammatory signaling pathways by the IL-1RA blocking of IL-1R1 (37,57,58). A recent study (59) showed that individuals with genotype 2/2 VNTR IL-1RN exhibited higher IL-1RA expression compared to 1/2 and 1/1 genotypes.…”
Section: Il-1rn Vntr Polymorphismmentioning
confidence: 99%
“…According to some studies the carriers of IL-1RN *2 have higher IL-1RA levels (53,55,56), and consequently the 2 allele effects could down-regulate IL-1 mediated pro-inflammatory signaling pathways by the IL-1RA blocking of IL-1R1 (37,57,58). A recent study (59) showed that individuals with genotype 2/2 VNTR IL-1RN exhibited higher IL-1RA expression compared to 1/2 and 1/1 genotypes.…”
Section: Il-1rn Vntr Polymorphismmentioning
confidence: 99%
“…Deubiquitinase cylindromatosis (CYLD) has been found to suppress NTHi-induced inflammation by inhibiting the expression of the key pro-inflammatory chemokine IL-8 via the MAP kinase phosphatase 1 (MKP-1)dependent inhibition of extracellular signal-regulated kinase (ERK) (Wang et al, 2014b). In a recent study, Zivkovic et al found that the IL-1RA VNTR allele 2 was associated with a chronic OM patient in Serbia and suggested that the allele is associated with higher IL-1RA levels, consistent with the increase in IL-1RA observed in mouse models of OM (Zivkovic et al, 2018).…”
Section: Genes Involved In Anti-inflammatory Responses In Ommentioning
confidence: 81%
“…It has an influence on numerous target cells, stimulating the pro-inflammatory network in the middle ear. Hence, it could result in the activation and proliferation of fibroblasts and the growth of osteoclasts in the middle ear, possibly leading to fibrosis and bone erosion 30 …”
Section: Discussionmentioning
confidence: 99%